Computer vision and image processing 4th International Conference, CVIP 2019, Jaipur, India, September 27-29, 2019, revised selected papers.: 4th International Conference, CVIP 2019, Jaipur, India, September 27-29, 2019, revised selected papers. Part I (©2020) - Unknown
No abstract available